PENGARUH MEDIA VLOG DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK SDIT SALSABILA 8 PANDOWOHARJO SLEMAN - Istikomah; Umi Faizah (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
Learning Natural Sciences experienced a decrease in value where 70% of students did not complete the KKM. Since the COVID-19 pandemic, learning has taken place online. Ineffective online learning makes learning outcomes go down. One of the reasons is that the online science learning process is not interesting. So an alternative solution is needed to overcome this problem, namely with Vlog media. The Vlog media has an effect on the science learning outcomes of the Force and Motion Relations material for the students of SDIT Salsabila 8 Pandowoharjo. This is obtained from the post-test results for the control class of 60.2 and the post-test results of the experimental class of 71.1. From these data, there is a difference in learning outcomes in the form of an average of 10.9. The effectiveness of the science learning Vlog media through the calculation results from the independent sample t-test post test, there is a sig (2-tailed) value of 0.008 with an average assumption of 109.35714. proven to be effective significantly and improve student learning outcomes in science learning the material Relationship of Style and Motion for class IV SDIT Salsabila Pandowoharjo Sleman